The Brexit vote, productivity growth and macroeconomic adjustments in the United Kingdom - Ben Broadbent; Federico Di Pace; Thomas Drechsel; Richard Harrison; Silvana Tenreyro (Bank of England, External Monetary Policy Committee Unit, 2019)
The UK economy has experienced significant macroeconomic adjustments following the 2016 referendum on its withdrawal from the European Union. This paper develops and estimates a small open economy model with tradable and non-tradable sectors to characterise these adjustments. We demonstrate that many of the effects of the referendum result can be conceptualised as news about a future slowdown in productivity growth in the tradable sector. Simulations show that the responses of the model economy to such news are consistent with key patterns in UK data. While overall economic growth slows, an immediate permanent fall in the relative price of non-tradable output (the real exchange rate) induces a temporary 'sweet spot' for tradable producers before the slowdown in tradable sector productivity associated with Brexit occurs. Resources are reallocated towards the tradable sector, tradable output growth rises and net exports increase. These developments reverse after the productivity decline in the tradable sector materialises. The negative news about tradable sector productivity also leads to a decline in domestic interest rates relative to world interest rates and to a reduction in investment growth, while employment remains relatively stable. As a by-product of our analysis, we provide a quantitative analysis of the UK business cycle.
Keywords: E13; E32; F17; F47; O16; 330; Brexit; small open economy; productivity; tradable sector; UK economy